A new double-slit rheometrical die for in-process characterization and extrusion of thermo-mechanically sensitive polymer systems - Teixeira, Paulo Francisco (2018)
The twin-slit rheological die can be operated in such a way that the total pressure drop is maintained constant while the shear rate in the measuring slit is changed. The device is particularly useful when coupled to an extruder and used to characterize materials that are sensitive to thermo-mechanical conditions. In the present work, the twin-slit die design was modified to a double-slit die where the measurement and extrusion channels have different geometries, and viscoelastic and morphological characterization can be performed. The flow analysis developed for twin channels was generalized to accommodate for different channel lengths and cross sections. The new set of equations was used to design the double-slit flow channel. Comparison of off-line with in-process data validated both the double-slit die and the experimental methodology. The practical utility of the new die was then demonstrated with the in-process rheological characterization of various polymer systems.